The pros and cons of safe electronuclear station with accelerator as a driver - Svistunov, Yu.A.; Vorogushin, M.F.; Gavrish, Yu.N.; Stepanov, A.V.; Kudinovich, I.V.; Struev, V.P. (Вопросы атомной науки и техники, 2001)
Creation of 200 MW compact safe energetic installation on a base of a high-temperature, gas-cooled, subcritical reactor was discussed in paper [1]. Chain reaction was initiated by the outer neutron flow. It was proposed to obtain such a source by irradiation of different substances with an intensive proton beam from the linac. Now possibilities of such a scheme are considered in more details. Structure of the reactor active zone is discussed. The use of the cyclotron as a driver is considered as an alternative variant. Problems of reliability, radiation safety and cost of installation are taken into account too.